Podometrics in Japanese Living Donor Kidneys: Associations with Nephron Number, Age, and Hypertension - Haruhara, Kotaro (J Am Soc Nephrol, 2021)
BACKGROUND: Podocyte depletion, low nephron number, aging, and hypertension are associated with glomerulosclerosis and CKD. However, the relationship between podometrics and nephron number has not previously been examined. METHODS: To investigate podometrics and nephron number in healthy Japanese individuals, a population characterized by a relatively low nephron number, we immunostained single paraffin sections from 30 Japanese living-kidney donors (median age, 57 years) with podocyte-specific markers and analyzed images obtained with confocal microscopy. We used model-based stereology to estimate podometrics, and a combined enhanced–computed tomography/biopsy-specimen stereology method to estimate nephron number. RESULTS: The median number of nonsclerotic nephrons per kidney was 659,000 (interquartile range [IQR], 564,000–825,000). The median podocyte number and podocyte density were 518 (IQR, 428–601) per tuft and 219 (IQR, 180–253) per 10(6) μm(3), respectively; these values are similar to those previously reported for other races. Total podocyte number per kidney (obtained by multiplying the individual number of nonsclerotic glomeruli by podocyte number per glomerulus) was 376 million (IQR, 259–449 million) and ranged 7.4-fold between donors. On average, these healthy kidneys lost 5.63 million podocytes per kidney per year, with most of this loss associated with glomerular loss resulting from global glomerulosclerosis, rather than podocyte loss from healthy glomeruli. Hypertension was associated with lower podocyte density and larger podocyte volume, independent of age. CONCLUSIONS: Estimation of the number of nephrons, podocytes, and other podometric parameters in individual kidneys provides new insights into the relationships between these parameters, age, and hypertension in the kidney. This approach might be of considerable value in evaluating the kidney in health and disease.